Effects of oil palm residues as bio-compost on growth performance of oil palm seedling / Anisah Mohammed ...[et al.] - Mohammed, Anisah; Jamali, Nuramalina; Yusop, Mohamad Amir Shah; Adip, Muhammad Esyam (2014)
Oil palm reach to uneconomical stage at 25 years old and replanting process will be carried out by felling the entire tree. Zero burning technique that been practices during replanting process contributed to the abundance of oil palm residue. The concept of zero burning is left the chipping and windrowed of oil palm residues to decay. Improper management of zero burning contribute to the breeding of Olycytes rhinoceros. Converting of oil palm residue to become valuable product through the composting process is one of the methods in managing the oil palm waste in the field. Compost of oil palm waste can be applied as the organic fertilizer especially in the growing of oil palm seedling. The objective of this study was to determine the effect of oil palm residues as bio compost to the growth performance of oil palm seedling. This study used 12 treatments and one control with designing by using Randomize Complete Block Design. Data collection on growth performance of oil palm seedlings were observes in terms of plant height, number of leave and stem girth for 12 weeks. Data were analysing by using Minitab version 16. The treatment of mixing empty fruit bunch and indigenous microorganism (T9) give the best result on plant height, plant girth and number of leaves. So this organic fertilizer can be suggested to be used in the field in improving the growth performance of oil palm seedling.